Cryosurgery with liquid nitrogen versus trichloroacetic acid in the treatment of human papillomavirus (HPV) penile wart: a randomized controlled trial - Morita, Mariana M. [UNESP]; Marcondes, Thomas S. P. [UNESP]; Haddad, Vidal [UNESP]; Miot, Hélio Amante [UNESP] (GN1 Sistemas e Publicacoes, 2021)
Background: Anogenital warts are the most prevalent sexually transmitted infection (0.5%) among dermatological consultations. Cryotherapy with liquid nitrogen (LN) and therapy with trichloroacetic acid (TCA) are remarkable among the treatment strategies. Objective: To evaluate the effectiveness of LN versus TCA in to treat penile warts in patients from a Brazilian public institution. Methods: Open, parallel, randomized clinical trial. Following randomization, the warts were counted and submitted to cryotherapy (10s) or case therapy (TCA 80%) in each visit. The primary dependent variable was the lesion count before and after four weeks of treatment. We assessed the following variables: complete clearance, age, immunosuppression, smoking, topography, and education. Results: 142 treatments were evaluated in 52 participants. There was a predominance of young adults, and the main topography affected was the penis shaft. The mean reduction rate per session was 48% for LN and 26% for TCA (p=0.11). 42 (81%) participants achieved complete clearance, with 39 (75%; 95% CI: 64-85%) reaching clearance in up to three sessions. Age was associated with a worse therapeutic response rate (ß =-0.09; p<0.01). Conclusions: LN and TCA proved to be effective to treat penile warts, without difference between treatments. Age was associated with a worse therapeutic response.
Criocirurgia com nitrogênio líquido versus ácido tricloroacético no tratamento de verruga peniana por papilomavírus humano (HPV): um ensaio clínico randomizado
Keywords: Cryosurgery; Papillomavirus infections; Sexually transmitted diseases; Trichloroacetic acid; Warts